Antibacterial activity of tannin-free ethanolic extracts from medicinal plants against methicillin-resistant Staphylococcus aureus - Pouria Nourmohammadi Ghezelghaye; Mostafa Alibegli; Amirabbas Fazelnejad; Ali Davoodi; Hamid Reza Goli (BMC Complementary Medicine and Therapies)
Abstract Background Treating infections caused by methicillin-resistant Staphylococcus aureus (MRSA) is a problematic challenge. This study aimed to evaluate the antimicrobial effect of some medicinal plantsʹ ethanolic extracts on MRSA strains. Methods Ethanolic extracts of the plants were prepared using the maceration method, and the total phenolic content (TPC) was measured by the Folin-Ciocalteu method. Total extractable tannins (TET) were removed by adding the polyvinylpolypyrrolidone (PVPP, 1.1 g) to plant extracts. The minimum inhibitory concentrations (MICs) of extracts against two clinical MRSA isolates and the ATCC 25,923 strain were determined using the micro broth dilution method. The minimum bactericidal concentrations (MBCs) of the extracts were determined by culturing on blood agar. Results The highest (453 ± 22.4 mg GAE/g) and lowest (3.5 ± 0 0.2 mg GAE/g) amount of TCP was detected in the root of Panax ginseng L. and the fruit of Amygdalus communis L., respectively. The highest extraction yield (165.5 ± 21.7 mg GAE/g) was observed in the flower of Humulus lupulus L. The MICs ranged from 0.078 to 5 mg/mL for MRSA isolates and from 0.001 to 2.5 mg/mL for the ATCC strain. The MBC level was 10 mg/mL for Rhus coriaria L. while its simultaneous use with Panax ginseng and the concurrent use of Amygdalus communis L. and Allium sativum L. showed a MIC range of 5 mg/mL. Conclusion Tannin-free ethanolic extract of Panax ginseng L., Rhus coriaria L., and Amygdalus communis L., and their simultaneous use with other extracts and erythromycin may be effective to control the growth of the MRSA strains.